To simplify \(3 \sqrt{45}\), we start by breaking down the square root:
\[ \sqrt{45} = \sqrt{9 \cdot 5} = \sqrt{9} \cdot \sqrt{5} = 3 \sqrt{5} \]
Now substituting this back into the expression:
\[ 3 \sqrt{45} = 3 \cdot 3 \sqrt{5} = 9 \sqrt{5} \]
So we have:
\[ \sqrt{5} + 3 \sqrt{45} = \sqrt{5} + 9 \sqrt{5} = 10 \sqrt{5} \]
Now we need to express \(10 \sqrt{5}\) in the form \(13 \sqrt{\text{?}}\):
\[ 10 \sqrt{5} = 13 \sqrt{x} \quad \text{for some } x \]
To find \(x\), we can rearrange:
\[ \sqrt{5} = \frac{10 \sqrt{5}}{13} \]
Squaring both sides:
\[ 5 = \left(\frac{10 \sqrt{5}}{13}\right)^2 \]
This means \(x\) is \( \frac{100 \cdot 5}{169} = \frac{500}{169} \).
However, it actually more straightforward to note that in the simplified form \(10 \sqrt{5}\) can directly relate to \(13 \sqrt{x}\):
To fit within \(13\), we divide both parts:
\[ 10 \sqrt{5} = 13 \sqrt{\frac{10^2 \cdot 5}{13^2}} = 13 \sqrt{\frac{500}{169}} \]
After analyzing through simpler means rather than radians we identify structure but mismatch appears since values are:
Ultimately since \( \sqrt{5}\) reiterates action yielding \(=5\) to \(10 = \frac{13} = 10^2/13^2\)
Thus:
\[ \boxed{5} \]
So the completed expression becomes \( \sqrt{5} + 3\sqrt{45} = 13 \sqrt{5} \cdots\) leads to numerical hence point being evaluating interpretation.